Perceptions of Students and Parents on Statutory Rape Bill - Ascrate, Glyza Mae; Delos Santos, Rhea; Posadas, Maricar; Gismundo, Great I Am W. (Southeast Asian Journal of Science and Technology, 2021)
Under the Anti-Rape Law of 1997, children with the age of 12 years old and above are seen as old enough to give sexual consent to adults which made the children vulnerable to sexual offenders as they can be manipulated due to their age. In this case, the House Bill 7836 is proposed to amend the current law and increase the age of consent from 12 years old to 16. This study was conducted to determine the perception of students and parents on statutory rape bill. The study was employed by descriptive research supplemented by survey questionnaire. In determining the significant differences between the respondents’ profile and their level of acceptability and awareness on statutory rape bill, independent t-test and one way ANOVA was utilized while Pearson’s correlation coefficient analysis was used to determine the significant relationship between the level of awareness and level of acceptability of the respondents.